Faktor-faktor yang Berhubungan dengan Kejadian ISPA pada Balita Berusa 6-24 Bulan di Wilayah Kerja Puskesmas Lebdosari Semarang - Maulida, Devina Alya; Darundiati, Yusniar Hanani; Nurjazuli (Universitas Widya Gama Mahakam, 2021)
Background: Acute Respiratory Infection is an infectious disease that occupies the first position of the top ten diseases of Lebdosari Community Health Center which are mostly suffered by the community, especially in infants with an incidence of 3.32%. Objectives: This Study aims to analyze the relationship sources of indoor air pollution and family practices to the incidence of Acute Respiratory Infection (ARI) in infants aged 6-24 months in the Lebdosari Community Health Center Semarang. Research Metodes: This study used a cross-sectional design. Sample size of about 121 toddlers taken by purposive sampling technique. Data was collected using self-administered questionnaire. Analysis of research was used chi-square test. Results: This study showed that there was a relationship between kitchen smoke (p-value = 0.029 RP = 2,676 95% CI = 1,296-5,527), the use of household insecticides (p-value = 0.045 RP = 2,974 95% CI = 1,329-6,653), presence of smokers in the house (p-value = 0.042 RP = 2,120 95% CI = 1,013-4,434), and opening windows practice (p-value = 0.001 RP = 3,191 95% CI = 1,589-6,409) with the incidence of ARI. There was no relationship between sun-curing bedding practice and hand-washing practice with the incidence of ARI. Conclusion: There was a relationship between kitchen smoke, the use of household insecticides, presence of smokers in the house, and opening windows practice with the incidence of ARI ARI in under five Children in The Works area of Lebdosari Community Health Center Semarang. Keywords: Acute Respiratory Infections (ARI), Under-Five Children, Lebdosari Community Health Center